ANALISIS KESALAHAN BAHASA (TAHLIL AL AKHTHA’) BUKU AJAR BAHASA ARAB MADRASAH IBTIDAIYYAH KELAS IV - Fathi Hidayah (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
The Arabic Language Textbook as a student guide to learn Arabic at Madrasah Ibtidayyah should present Arabic material that is in accordance with the gramatical of the Arabic language. However, it turns out that many errors were found both in terms of morphology, syntax and choice of words used in sentences. This error becomes a fatal thing if there is no evaluation of the textbook because it is at the basic level in learning language. This study uses a literature research design with tahlil akhta analysis as a technical data analysis. The results showed that 4 types of language errors were found in the Arabic language textbook for Class IV Madrasah Ibtidayyah, namely morphological, syntactic, morpho-syntactic and semantic errors.